Rancang Bangun Kemasan Kotak Plastik Persib Serbaguna Menggunakan Vacuum Forming - Ramdani, Rizki (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2023)
Currently, there is no Persib packaging box on the market. The characteristic in question is the presence of the Persib Bandung logo on the packaging. This box packaging will be useful for various purposes (multipurpose), ranging from food containers, attributes, souvenirs etc. With the Persib logo on this packaging, it will certainly add to the attractiveness, especially for Bobotoh. The purpose of this research is to design a multipurpose Persib plastic box packaging mold, to make a mold for multipurpose Persib plastic box packaging and to make multipurpose Persib plastic box packaging. The problem limitation in this research is the mold design process using computer aided design, using Siemens NX Software. The stages carried out include; the CAD process of making mold designs using NX-Siemens, the CAM simulation process and generating G-Code for the CAD program that has been made, the mold manufacturing process using a 3-axis CNC milling machine, the mold testing process on a vacuum forming machine and evaluating the results of a multipurpose Persib plastic box packaging product. The results of the product are largely in accordance with the desired, but there are some details that are not maximized